Gestión y desarrollo Turístico en el Cantón Guamote, Provincia de Chimborazo - Proaño Lucero, Gabriela Elizabeth (2019)
This research work focuses on the study of the management of the Gobierno Autónomo Descentralizado del Cantón Guamote, within the tourism unit in order to help strengthen local tourism development. It was based on situational analysis, detecting flaws and proposing improvement strategies to preserve tradition and culture. In addition, to revaluing natural heritage considering the entity as a public company. It tended to improve the provision of services to enhance tourism in the Canton. To get information, it was considered the taking of samples from the populations as a record of the service providers and the economically active population. To know the existing reality in the territory for making decisions that satisfy the needs of the sector with viable proposals that allow even more to increase the institutional image of the municipality. The methods used are documentary, field and correlation, in terms of the design of the research is quali - quantitative. The statistical processes were carried out in the software SPSS, version 25; as the Cronbach's Alpha that determined the reliability of the instruments, the analysis and interpretation of the results; and finally the verification of the hypothesis with chi-square, determining the dependency between management and tourism development. With the results of the surveys, the prepositive framework was applied, where a Tourism Management Model was proposed for the canton of Guamote, the province of Chimborazo, which contains strategies and actions for tourism development. Subsequently, it is possible to determine if there is a management and planning model for participatory local development, directed to the Tourism Unit so that the competences are fulfilled. It is recommended that the authorities in turn within the municipality put in the place of management to promote the development of local capacities. Besides, to implement in tourism as a tool to improve the quality of life of the population.